2020
DOI: 10.1111/myc.13120
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Aspergillus invasive mould infections in patients treated with ibrutinib

Abstract: Summary Background Invasive mould infections (IMIs) are very rare in patients with lymphoid malignancies. However, IMIs, mostly due to Aspergillus species, have been increasingly reported in such patients receiving ibrutinib (IBR). There is paucity of information regarding non‐Aspergillus invasive mould infections (NAIMIs) in this setting, Objectives To review our recent experience and the published literature on the topic. Patients/Methods We present a case of invasive sinusitis caused by Fusarium in a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…Epidemiologic studies reported an increase in the incidence IFD in patients with CLPDs receiving ibrutinib, especially invasive aspergillosis (IA) [25]. However, other IFDs, including invasive fusariosis, have also been diagnosed in such patients [26,27].…”
Section: Settingmentioning
confidence: 99%
“…Epidemiologic studies reported an increase in the incidence IFD in patients with CLPDs receiving ibrutinib, especially invasive aspergillosis (IA) [25]. However, other IFDs, including invasive fusariosis, have also been diagnosed in such patients [26,27].…”
Section: Settingmentioning
confidence: 99%
“…However, in recent years, IFD has been increasingly reported in other populations, such as those with acute lymphoblastic leukaemia, lymphoma or multiple myeloma. This holds especially true in those patients who have received multiple prior lines of treatment [ 17 , 18 ]. IFD epidemiology in patients with haematological malignancies has been highly influenced by the widespread introduction of antifungal prophylaxis in high-risk populations [ 2 ].…”
Section: Non- Aspergillus Mould Infections In Spec...mentioning
confidence: 99%
“…28 Fungal infections, although rarely reported in clinical trials, have also been associated with the use of ibrutinib in several observational studies; 13,[28][29][30][31][32] the most common causative agent was Aspergillus spp., although non-Aspergillus infections have also been reported. 33 Inhibition of the BTK pathway in macrophages involved in the defence against fungi may play a role. 32,34 Fungal infections typically appear during the first 6 months of treatment, in patients who have received previous antineoplastic treatment, and in those receiving glucocorticoids.…”
Section: Bruton Tyrosine Kinase Inhibitorsmentioning
confidence: 99%